2011
DOI: 10.1007/s11632-011-0207-6
|View full text |Cite
|
Sign up to set email alerts
|

Composition and diversity of five major forest types in moist temperate climate of the western Himalayas

Abstract: The present study was undertaken in fi ve major forest types (dominated by Quercus semecarpifolia, Quercus fl oribunda, Acer acuminatum, Abies pindrow and Aesculus indica, respectively) between 2400 and 2850 m a.s.l. in a moist temperate forest of the Mandal-Chopta area in the Garhwal region of Uttarakhand, India. The aim was to assess the variation in composition and diversity in different vegetation layers, i.e., herb, shrub and tree, among these fi ve forest types. Diversity indices, such as the Shannon-Wie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
5
14
1
Order By: Relevance
“…The dead wood matter (woody debris) on the forest floor supplies enough nutrients to sustain forest diversity. These TBC values are higher than earlier reported values of 41.25 m 2 ha ¡1 by Gairola et al (2011) and 35.66 m 2 ha ¡1 by Singhal et al (1986), but similar to the recorded TBC values of 54-124 m 2 ha ¡1 (Baduni 1996), 67.84-115.18 m 2 ha ¡1 , and 84.03 m 2 ha ¡1 ) from various regions of Garhwal Himalaya.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The dead wood matter (woody debris) on the forest floor supplies enough nutrients to sustain forest diversity. These TBC values are higher than earlier reported values of 41.25 m 2 ha ¡1 by Gairola et al (2011) and 35.66 m 2 ha ¡1 by Singhal et al (1986), but similar to the recorded TBC values of 54-124 m 2 ha ¡1 (Baduni 1996), 67.84-115.18 m 2 ha ¡1 , and 84.03 m 2 ha ¡1 ) from various regions of Garhwal Himalaya.…”
Section: Discussionsupporting
confidence: 84%
“…Gairola et al (2011) also referred A. acuminatum as the dominant species in A. pindrow forest (2500-2600 m a.s.l.). However, in this study, A. acuminatum was not recorded as the top dominant species due to lower importance value and limited population size which was found growing well with A. pindrow.…”
Section: Discussionmentioning
confidence: 99%
“…The recorded diversity index values were lesser to the earlier reported values i.e., 2.66 for Q. leucotrichophora; 2.53 for Q. floribunda and 1.41 for Q. semecarpifolia forests (Singh and Rawat 2012), 1.2 to 2.7 for Q. floribunda forest (Kumar and Ram 2005), 0.76 to 1.50 for Q. floribunda forest (Lodhiyal et al 2013). However, Gairola et al (2011) have reported the diversity index values as; 0.46 for Q. semecarpifolia forest and 0.49 for Q. floribunda forest, which were closer to our values. The herb diversity was more than trees and shrubs in all the Oak forests ( Table 1).…”
Section: Plant Diversitysupporting
confidence: 89%
“…Our values are best fitted with the previously reported values for biomass production i.e., 387. Q. semecarpifolia forest at 2,650-2,850 m asl were also reported by Gairola et al (2011) for Oak mixed forests. However, the biomass production of 272.…”
Section: Biomass and Carbon Storagesupporting
confidence: 75%
“…Sumeet et al [16] noted that findings from studies that address patterns of plant distribution and dynamics of biological resources can provide a rational basis for planning and making decisions about the environment. Otherwise, restoration of resources in their natural habitat would be very difficult [17].…”
Section: Introductionmentioning
confidence: 99%